The relationships between students’ comprehension of conversational implicatures and their achievement in reading comprehension - Çiftlikli, Safiye; Demirel, Özcan (Frontiers in Psychology, 2022)
The most important thing in effective communication is understanding not only what is said, but also why it is said. Therefore, the development of pragmatic competence in another language is essential to be able to communicate effectively. Pragmatic competence plays an important role in enabling interlocutors to work out what is intended by what is said. In this sense, special emphasis should be placed on the pragmatic aspects of language in order to enable language learners to use language appropriately. In this regard, this study aims to investigate whether there is a relationship between students’ comprehension of conversational implicatures and their achievement in reading comprehension. To this end, the data were collected from first-year 122 students at one of the private universities in northern Cyprus with different bachelor’s degrees via the Multiple-Choice Discourse Completion Test (MCDCT) and the reading test. The quantitative data were analysed by means of A Pearson Correlational Analysis, Simple Linear Regression, and Canonical Correlational Analysis. The results of the study revealed that comprehension of conversational implicatures of first-year university students is positively related to their achievement in reading comprehension. Moreover, it has been depicted that among the eight implicature types, topic change, indirect refusal, and disclosure are more related (.855) to reading comprehension. Therefore, these three implicature types provide the most contribution to the participants’ comprehension of conversational implicatures. As it is, they are more powerful predictors of reading comprehension. In addition to these results, there is only one high positive correlation among the six reading subskills; that is between the subskill to identify ideas and opinions of the writer and the subskill to scan a text to find specific information (.749). In the light of the findings, this study yields crucial implications for language teachers, material developers, and curriculum designers to take full advantage of these associations for promoting EFL learners’ achievement in reading and comprehension of conversational implicatures in the target language.